Legal protection of passengers in a train accident - Dhina Setyo Oktaria; Akbar Zulkarnain (Institute Of computer Science (IOCS), 2024)
Train accidents consist of train-to-train collisions, derailments, rollovers, and fires. Legal protection for train accident victims has an essential role so that the victims' rights are protected. The method used in this research is the Legal Research Method with Juridical Review. Legal protection for train accident victims is contained in the 1945 Constitution, and regulations from the Ministry of Transportation include Law No. 23 of 2007, Government Regulation No. 62 of 2013. There is also a separation of powers between the government and train operators related to their duties and authority in responsibility for train accidents and train accident victims. The results obtained were that apart from the statutory regulations governing railway accidents, there was a need for a unified system between technical operations, human resource capabilities in the railway sector, and public awareness as train users.